Cognitive dysfunction in Malaysian patients with major depressive disorder: A subgroup analysis of a multicountry, cross‐sectional study - Zainal, Nor Zuraida; Kalita, Pranab; Herr, Keira Joann (Wiley, 2019)
Introduction: Cognitive dysfunction has been significantly associated with functional impairment in patients with major depressive disorder (MDD). Methods: This is a subgroup analysis of 211 Malaysian patients recruited from the multicountry, multicenter, cross-sectional Cognitive Dysfunction in Asian patients with Depression (CogDAD) study. Depression severity, cognitive dysfunction, and functional disability were assessed and compared with the overall CogDAD study population. Factors associated with functional disability were also evaluated in this Malaysian patient population. Results: Approximately half of the Malaysian patients were in their first depressive episode, with the majority being treated for mild-to-moderate depression. Furthermore, Malaysian patients experienced cognitive dysfunction, with self-reported Perceived Deficits Questionnaire (PDQ-D) scores falling within the third quartile of PDQ-D severity. Malaysian patients also reported functional disability evidenced by a mean total Sheehan Disability Scale (SDS) score of 11.47 ± 6.68, with the highest SDS score reported in the “Social Life/Leisure Activities” domain. Compared with the overall CogDAD study population, the Malaysian patient population had comparable patient demographics in terms of marital and working status; outcome scores for PHQ-9 (9-item Patient Health Questionnaire for self-reported depression severity), PDQ-D and SDS; and worst perceived cognitive dysfunction reported in the “Attention/Concentration” domain. Factors found to be significantly associated with functional disability were PDQ-D score, sick leave taken, and antidepressant treatment (P < 0.05). Discussion: Findings from this subgroup analysis highlight the significance of treating cognitive dysfunction in patients with MDD and its correlation to functional disability.